Life history of the maritime platygastrid Echthrodesis lamorali Masner 1968 (Hymenoptera: Platygastridae: Scelioninae) - Owen, Candice Ann (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2016)
Echthrodesis lamorali Masner 1968 (Hymenoptera: Platygastridae, Scelioninae) is an intertidal parasitoid wasp that uses the eggs of the maritime spider, Desis formidabilis O.P. Cambridge 1890 (Araneae: Desidae), as a host. This species is one of only three known maritime parasitoids globally, and is the only known spider egg parasitoid that attacks its host within the intertidal region in southern Africa. Originally described from 'The Island', Kommetjie (Western Cape, South Africa), this shore was the only known locality of the species at the commencement of this thesis. Furthermore, the extent of the parasitism pressure the wasp exerts on D. formidabilis was largely unknown, along with its basic biology (drivers of its broad-scale and fine-scale distribution patterns; parasitism incidence; and sex ratios) and morphological and physiological adaptations for living within the frequently saltwater-inundated environment. This thesis unravelled these aspects, as well as experimentally provided data for many components of the life history of E. lamorali that had only been hypothesized by other authors, at a variety of scales, from the country-wide ecosystem, to single shores, and finally to the scale of the individual. While the distribution of E. lamorali was found to be much wider than previously thought, it remained restricted to the shores of the Cape Peninsula (Western Cape, South Africa). The host spiders were located throughout a much wider distributional range than the wasp, from East London in the east to the Peninsula, but some behavioural and morphological differences were found between those within and outside of the range of the parasitoid, suggesting range-limitation imposed by the host on E. lamorali. This limitation may be strengthened by the general lack of suitable shore types within the close vicinity of the Peninsula. Modelling using macro-climatic conditions suggested that maximum temperatures and humidities were also largely limiting to E. lamorali, although these patterns were not observable in the micro-climates in which the species survives. The wasp populations and spiders within the range of E. lamorali as identified in Chapter 2 were assessed to determine any preferences for local conditions, including location along the Peninsula, nesting sites and intertidal zones within single shores, using AICc modelling, which detected parasitism patterns in D. formidabilis and E. lamorali populations, as well as the sex ratios in the latter species. The models showed that the spider population size and distribution was more influenced by bottom-up factors such as abiotic components of the shore than by parasitism, which only showed density dependence with the host at certain scales. Both host and parasitoid populations illustrated a preference for the middle zone on single shores. Observed spider nest characteristics suggested opportunistic nesting behaviour in the species, although preference was shown for construction along an east-west orientation and in locations with low sun exposure. Along with larger population sizes on the west coast over the east coast (not reflected by E. lamorali), these observations suggest that D. formidabilis prefers cooler environments. Spider brood success was 50% in unparasitized egg-sacs, but this figure halved when E. lamorali gained access to the eggs (of which 100% within a single compartment were parasitized each time). Encapsulation of the embryo was found to be positively correlated with parasitism, indicating some form of host resistance. Resultant parasitoid broods illustrated a strong female bias in the species, as is common for this group of insects. The life history of E. lamorali was then assessed at a smaller scale, that of the individual. Scanning electron microscopy of whole E. lamorali specimens and light microscopy of sectioned specimens demonstrated no morphological adaptations in the trachea and spiracles to cope with saltwater inundation. On the other hand, respirometry experiments categorically demonstrated that the species copes with inundation through the formation of a physical gill over the full habitus, and the induction of a state of torpor to reduce metabolic needs, when submerged. This precludes the need for any further morphological adaptations. Determination of the wasp's critical thermal tolerance illustrated a wide temperature range with a particularly cold lower limit of -1.1ÂºC Â± 0.16, suggesting the presence of related genera or ancestors in much colder environments. With a much broader distribution than previously thought, and the inclusion of the distributional range of E. lamorali within the Table Mountain National Park, this species is being effectively conserved and managed through the umbrella-conservation of the park. Links to the host proved to vary at differing scales, proving the need for scale considerations to be included in other similar biological and ecological studies. Finally, the species showed physiological adaptation to its intertidal existence. Echthrodesis lamorali, the only discovered maritime spider egg parasitoid in Southern Africa, displayed unusual characteristics at every scale of its life history and as such, warrants further investigation.
Keywords: Uncatalogued